Hubungan Body Mass Index (BMI) dengan CTDIVOL dan DLP pada Pemeriksaan Ct-Scan Kepala di Klinik Utama Bunga Emas Denpasar - Gede Agus Susila Dharma (Syntax Corporation Indonesia, 2024)
The research aims to analyze the relationship between Body Mass Index (BMI), CTDIvol, and DLP in head CT scan examinations at Bunga Emas Primary Clinic, Denpasar, with the goal of understanding the influence of CTDIvol and DLP on BMI in head CT scans at Bunga Emas Primary Clinic, Denpasar. This study employs a quantitative research design with an experimental approach conducted at Bunga Emas Primary Clinic, Denpasar, from April to May 2023. The study population consists of all individuals who underwent head CT scan examinations, with a sample size of 30 individuals selected from Bunga Emas Primary Clinic, Denpasar. Data were recorded in a worksheet for subsequent calculations. Based on the research findings, it was determined that there is no influence of BMI on CTDIvol and DLP values. Considering several statistical tests conducted, such as the Spearman correlation test, which yielded a p-value (2-tailed) of 0.120 (p > 0.05) for BMI with respect to CTDIvol, and a p-value (2-tailed) of 0.320 (p > 0.05), indicating that the null hypothesis (H0) is accepted while the alternative hypothesis (Ha) is rejected. This is likely due to the head having less variation in size and composition compared to other body parts, such as the chest or abdomen.